A new manual method for assessing elbow valgus laxity - Yasui Kenji; Mihata Teruhisa; Takeda Atsushi; Watanabe Chisato; Kinoshita Mitsuo (BMC, 2012)
Abstract Background A screening of ulnar collateral ligament insufficiency is required for overhead throwers, since secondary pathologic changes result from an increased elbow valgus laxity. We developed a new manual method for assessing elbow valgus laxity and investigated the reliability of this method and its correlation with ultrasonographic assessment. Methods We defined elbow valgus laxity as the difference between the shoulder external rotation angle (ER angle) measured with the elbow in 90 degrees flexion and that measured with the elbow in extension because ER angle measured with the elbow in 90 degrees flexion includes elbow valgus laxity and ER angle with the elbow in extension does not include it. ER angle measurement with the elbow in extension involved the use of a custom arm holder. Three examiners each measured elbow valgus laxity by the new method in 5 healthy volunteers. Intraobserver and interobserver reliability was evaluated by calculating the intraclass correlation coefficient. We then assessed 19 high-school baseball players with no complaints of shoulder or elbow pain. Elbow ultrasonography was performed with a 10-MHz linear transducer with the elbow in 90 degrees flexion, and the forearm in the neutral position, and the width of the medial joint space at the level of the anterior bundle was measured. Elbow valgus laxity assessed by ultrasonography was defined as the difference between the medial joint space width with gravity stress and that without gravity stress. Increased elbow valgus laxity assessed by both our method and ultrasonography was defined as the difference between the laxity of the elbow on the throwing side and that on the contralateral side. Pearson's correlation coefficient (r) was calculated to evaluate the relationship between increased elbow valgus laxity obtained by our manual method and that by ultrasonography. Results Intraobserver reliability ranged from 0.92 to 0.98, and interobserver reliability was 0.70. The increased elbow valgus laxity assessed by our method was significantly correlated with that assessed by ultrasonographic assessment (P = 0.019, r = 0.53). Conclusions Elbow valgus laxity can be assessed by our method. This method may be useful for screening for insufficiency of the ulnar collateral ligament.